= 72y^4 - 81y^3 + 27y^2 - 72y^2 + 81y - 27
(can you see what I did ?)
= 72y^4 - 81y^3 - 45y^2 + 81y - 27
(the y^2's were the only "like" terms )
I wrote the problem wrong...
then go with the first part of my 'THEN'
Now it is easier
just multiply the y^2 by each of the terms inside
= 8y^4 - 9y^3 + 3y^2
All done, since none of the terms are "like"
and that's it??? That's right, it cannot be simplified b/c of no like terms!!!
intermediate algebra - Find the product. -9y^2(y^4+8y^3-y^2+8y+7)
Math - Which of the following expressions is the simplified form of 3y+8y-4+7-...
Math - Could someone please explain this problem to me. I need to factor and ...
Algebra - -8y+1=-9y+2
algebra 1 - I'm stuck on this problem. Can you help? -4x-9y=1 -x + 2y =-4 WHat ...
Algebra - Factor completely: x^10y^3 – 4x^9y^2 – 21x^8y
maths - y-(7-8y)/9y-(3+4y)=2/3
math - x=6y/5-8y-3y+9y,what is the value of y in terms of x ?
Algebra 1 - x+9y=8 (1) x=3-9y (2) x (3-9y)+9=8 3x -9y +9y=8 3x = 8 x= 2.6 Is ...
math - when question ask subtract (5y+8y+2) from (7y+9y-8) which expression ...